(1139) Fife Model in French Planning نموذج فايف في التخطيط الفرنسي - ullmo, bernard (the institute of national planning, 2018)
the word mixed economy applies only partly to the french to the situation: for the productive sector is mostly operating under the general conditions of a free competitive system, as the majority of firms are private-owned and managed.